Fasciola hepatica Immune Regulates CD11c+ Cells by Interacting with the Macrophage Gal/GalNAc Lectin - Rodríguez, Ernesto; Carasi, Paula; Frigerio, Sofía; da Costa, Valeria; van Vliet, Sandra; Noya, Verónica; Brossard, Natalie; van Kooyk, Yvette; García-Vallejo, Juan J.; Freire, Teresa (Frontiers in Immunology, 2017)
Fasciolosis, caused by Fasciola hepatica and F. gigantica, is a trematode zoonosis of interest in public health and livestock production. Like other helminths, F. hepatica modulates the host immune response by inducing potent polarized Th2 and regulatory T cell immune responses, and by down-regulating the production of Th1 cytokines. In this work we show that F. hepatica glycans increase Th2 immune responses by immune modulating TLR-induced maturation and function of dendritic cells (DCs). This process was mediated by the Macrophage Gal/GalNAc Lectin (MGL) expressed on DCs, that recognizes the Tn antigen (GalNAc-Ser/Thr) on parasite components. More interestingly, we identified MGL-expressing CD11c+ cells in infected animals and show that these cells are recruited both to the peritoneum ant the liver upon F. hepatica infection. These cells express the regulatory cytokines IL-10, TNF and TGF and a variety of regulatory markers. Furthermore MGL+ CD11c+ cells expand parasite-specific Th2/regulatory cells and suppress Th1 polarization. The results presented here suggest a potential role of MGL in the immune modulation of DCs induced by F. hepatica, and contribute to a better understanding of the molecular and immune regulatory mechanisms induced by this parasite.